Assessment Influence of Microwave Heating on a Physical Properties of Dried Clay Bricks Compared with Conventional Methods - Bagaber, Salem Abdullah; Izman, Sudin (Universiti Malaysia Pahang, 2016)
The current state of brick manufacturing process is still very traditional where drying of clay brick takes very long time and labour intensive. Adding to this problem, uneven heating during drying and firing affect a lot to bricks quality which often cause cracks. This paper aims to evaluate the effectiveness of microwave energy source against the conventional methods for drying clay bricks. Green clay samples were pressed into a slab specimen at different compositions (%red clay, %water, %charcoal). Later, the green samples were dried under four different heat methods (natural, hot air, electric oven and microwave). The quality of dried bricks was compared in terms of water absorption, density, and crack. From the results obtained, it is concluded that microwave technology has a great potential to be applied as a heating source in the production of bricks. The usage of this technology is foreseen able reduce the intensive labour dependent in brick manufacturing industry and this method is able to manufacture brick in a more sustainable environment.